Вопрос исследования абстрактных существительных в русском языкознании - Даулетбаев, М (SCIENCE and SOCIETY, 2025)
Abstract nouns are among the lexemes that are interesting and cause difficulties in learning. Be- cause abstract concepts occupy a central place in the thinking of any nation. In general, since a person tends to name things, phenomena that surround him, it is quite natural that he refers to the genus of nouns in this. Concepts free
Keywords: abstract nouns; sense organs; linguistics; abstraction; thinking; language; term